Singapore Management University launches its first overseas centre in Jakarta - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
Singapore Management University (SMU) today opened its first overseas centre in Jakarta, Indonesia, bolstering the university’s goal to positively impact local communities as it advances its "Growth in Asia" strategic priority as part of its Vision 2025.